Traces of Banyuwangi Women's History: From Past to Present - Oktavias, Feny; Mahfud (CV. Sekawan Siji, 2024)
Women in Banyuwangi, Indonesia, have a rich and complex history that includes a long history of women's leadership and empowerment. This paper focuses on the history and achievements of women in the area, focusing on the challenges they have faced and the strategies they have used to overcome them. The historical perspective allows us to gain a deeper understanding of the systemic barriers that have hindered their progress and their strategies for addressing contemporary issues related to gender equality. Gender equality is not just a women's issue, but a societal issue that requires collective action and commitment. By recognizing and addressing the systemic barriers that hinder women's progress, we can create a more inclusive and equitable society for all.